Ordinance No. 13, §§ 1 & 7, Othello Town Council (1911) (Othello, Washington). - (:unkn) unknown (My University, 1911)
All persons (except police officers and other persons whose duty it is to execute process or warrants or make arrests) who shall carry upon their persons any concealed weapons, consisting of a revolver, pistol or other firearms (except by written permit from the Chief of Police) or any knife (other than an ordinary pocket knife) or any dirk or dagger, sling shot or metal knuckles or any instrument by the use of which in§jury can be inflicted upon the person or property of any other person. All persons (except peace officers as aforesaid) who shall draw, exhibit or attempt to use any deadly weapon upon, to or against another person within said town with intent to do bodily injury to such person. All persons (except peace officers as aforesaid and persons practicing at target shooting in a shooting gal§lery, duly licensed) who shall in the town limits fire off or discharge any gun or pistol or firearm of any kind, or bomb...
Keywords: BRANDISHING; CARRY - CONCEALED